Exploring the intersection of brain injury and mental health in survivors of intimate partner violence: A scoping review - Toccalino, Danielle; Moore, Amy; Cripps, Elizabeth; Gutierrez, Sophia Chuon; Colantonio, Angela; Wickens, Christine M.; Chan, Vincy; Nalder, Emily; Haag, Halina (Lin) (Frontiers in Public Health, 2023)
Rationale Intimate partner violence (IPV) is the most commonly occurring form of violence against women. The most common site of injury in IPV is the head, face, and neck, resulting in possible brain injury (BI). Independently, mental health (MH) concerns are highly prevalent among both IPV survivors and individuals with BI; however, no systematic review exists on the combined experience of BI and MH in IPV. Objective The aim of this review was to describe the identification of and relationships between BI, MH, and IPV in the literature and the implications for health policy and practice. Methods A search strategy including text words and subject headings related to BI, IPV, and MH was developed for MEDLINE and translated to EMBASE, PsycINFO, CINAHL, Cochrane, Scopus, and Web of Science. Two reviewers independently assessed articles for inclusion. Articles discussing MH, BI, and IPV in relation to one another were included in the review. Results Twenty-eight articles were identified for inclusion. Methods for identifying IPV, BI, and MH were highly variable across studies. Fourteen studies reported significantly higher MH scores in IPV survivors with BI than in those without BI. Articles predominantly focused on cis gender women in heterosexual relationships and the impact of race and ethnicity were largely overlooked. Healthcare access was explored by eight articles, though none discussed the implications of co-occurring BI and MH. Conclusion Brain injury and MH are highly prevalent among IPV survivors; however, little research discusses the implication for healthcare. Future research should explore healthcare-related needs and experiences to inform policy and practice and better represent the diversity of IPV survivors.